The management of an early-missed abortion after radical trachelectomy—a case report and a review of the literature. Issue 4 (1st July 2006) - Lavie, O.; Peer, G.; Sagi, S.; Ben Arie, A.; Auslender, R.
Abstract : Radical trachelectomy (RT) has been reported for almost 20 years. This case report describes and addresses the issue of the clinical management of early-missed abortion in a patient after RT with a cerclage. Case: A 35-year-old woman who had a RT 2 years ago due to cervical carcinoma stage IB1 presented with a missed abortion of an 8-week gestational age. At the end of the RT, a cerclage suture was inserted in the remaining internal oss of the cervix. The patient went through a cervical dilatation followed by suction curettage guided by ultrasonography without compromising the cerclage. This case report suggests that dilatation and suction curettage without compromising the cervical cerclage is a feasible option in the clinical management of early abortion in a patient after RT.